The midnight house - Berenson, Alex. (New York : G.P. Putnam's Sons, 2010)
Summoned to Langley in the aftermath of two murders, CIA agent John Wells learns that the victims were part of a secret interrogation team that used brutal methods to break tough jihadis, a case with ties to unexpected places.
Keywords: United States. -- Central Intelligence Agency -- Fiction; Intelligence officers -- Fiction; Terrorists -- Fiction; Suspense fiction